2021
DOI: 10.3390/pathogens10070881
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of an Aberrant Mucosal Immune Response to SARS-CoV-2 in the Pathogenesis of IgA Nephropathy

Abstract: The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global concern. Immunoglobin A (IgA) contributes to virus neutralization at the early stage of infection. Longitudinal studies are needed to assess whether SARS-CoV-2-specific IgA production persists for a longer time in patients recovered from severe COVID-19 and its lasting symptoms that can have disabling consequences should also be alerted to susceptible hosts. Here, we tracked the anti-SARS-CoV-2 spike protein recept… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In our single-center cross-sectional study of 72 consecutive patients with active glomerulonephritis requiring immunosuppressants reviewed in the Glomerulonephritis Disease Management Clinics between June and August 2021, 49 (68.1%) participated in the selfadministered English-language questionnaire for determinants of vaccine acceptance recommended by the World Health Organization framework. 4 Among the 19 men and 30 women, the median age was 47.3 (interquartile range 30.5-60.2) years with diagnoses including lupus nephritis (18 patients), primary podocytopathies or membranous nephropathy (17 patients), Immunoglobulin A nephropathy (nine patients) and other glomerular diseases (five patients) and median disease duration of 45 (32-79) months. English was spoken at home and to healthcare workers in 69.4% and 85.7%, respectively.…”
Section: Covid-19 Vaccine Acceptance Among Patients With Glomerulonep...mentioning
confidence: 99%
See 1 more Smart Citation
“…In our single-center cross-sectional study of 72 consecutive patients with active glomerulonephritis requiring immunosuppressants reviewed in the Glomerulonephritis Disease Management Clinics between June and August 2021, 49 (68.1%) participated in the selfadministered English-language questionnaire for determinants of vaccine acceptance recommended by the World Health Organization framework. 4 Among the 19 men and 30 women, the median age was 47.3 (interquartile range 30.5-60.2) years with diagnoses including lupus nephritis (18 patients), primary podocytopathies or membranous nephropathy (17 patients), Immunoglobulin A nephropathy (nine patients) and other glomerular diseases (five patients) and median disease duration of 45 (32-79) months. English was spoken at home and to healthcare workers in 69.4% and 85.7%, respectively.…”
Section: Covid-19 Vaccine Acceptance Among Patients With Glomerulonep...mentioning
confidence: 99%
“…1,2 The mechanism of IgA nephropathy post SARS-CoV-2 infection remains to be elucidated; however, continuous IgA production after SARS-CoV-2 infection may occur. 3,4 There is a possibility of developing new nephritis as well as exacerbation of existing nephritis after SARS-CoV-2 infection, necessitating a careful follow-up.…”
Section: New-onset Immunoglobulin-a Nephropathy Post Severe Acute Res...mentioning
confidence: 99%
“…Huang et al found that the levels of IL-1β, IL-1RA, IL-6, IL-7, IL-8, IL-9, IL-10, macrophage colony-stimulating factor (M-CSF), IFN-γ, platelet-derived growth factor (PDGF), TNF-α and vascular endothelial growth factor (VEGF) in COVID-19 patients were higher than those of healthy subjects, suggesting that cytokine storm was related to the occurrence of extrapulmonary multiple organ dysfunction during the progression of COVID-19 [3,39,40]. Following-up and monitoring of 173 COVID-19 patients after recovery and discharge, it is found that 52.3% of patients have a mucosal immune response dominated by IgA, accompanied by increased serum creatinine, worsening proteinuria, and elevated levels of pro-inflammatory cytokines such as IL-18 [41,42].…”
Section: Cytokine Stormmentioning
confidence: 99%
“…More and more studies indicate that the gut-kidney axis may be involved in the pathogenesis of many diseases. There are some studies ( 13 16 ) have reported intestinal microbiome dysregulation in IgAN patients. Additionally, changes in the composition of the intestinal microbiota and increased IgA highly coated bacteria were indicative of potential involvement of intestinal dysbiosis to the systemic IgA level and, consequently, the IgAN progression.…”
Section: Role Of Gut-kidney Axis In Iga Nephropathymentioning
confidence: 99%